Antioxidant and antimicrobial efficacy of watermelon rind extract (WMRE) in aerobically packaged pork patties stored under refrigeration temperature (4±1°C). Issue 10 (25th September 2018) - Kumar, Pavan; Mehta, Nitin; Malav, O. P.; Kumar Chatli, Manish; Rathour, Manjeet; Kumar Verma, Akhilesh
Abstract : The present study was undertaken to evaluate antioxidant and antimicrobial efficacy of ethanolic extract of watermelon rind (WMRE) incorporated at 0.10% level in pork patties. The selected patties along with positive control (with 0.02% butylated hydroxyl anisole) and control samples were packaged in aerobic packaging and evaluated for various oxidative and microbiological stability parameters for 28 days under refrigeration (4 ± 1°C). The indicators of lipid peroxidation viz. thiobarbituric acid reactive substances (TBARS), free fatty acids (FFA) and peroxide value (PV) showed an increasing trend for control as well as treated products; however, treated product showed a significantly (P < 0.05) lower value than control. Microbiological and sensory qualities were maintained better for treatment throughout storage period. Thus, WMRE has potential to enhance storage stability of aerobically packaged pork patties stored at refrigeration temperature (4 ± 1°C) owing to its antioxidant and antimicrobial potency. Practical applications: A huge quantity of watermelon rind is generated each year from watermelon fruit industry and their proper disposal remains a major environmental concern. The rind is very rich source of valuable bioactive compounds exerting antioxidant and antimicrobial effect. By harvesting through suitable extraction protocols and innovative processing technologies, these compounds could be utilized in developing functional meat products with higher antioxidant and antimicrobial properties, resulting in their improved oxidative stability and extension of storage life. This would also ensure profitable returns to farmers and proper disposal of watermelon rind thus ushering overall integrated development of agro‐meat industry.